Studies of shorebirds at Lindisfarne, Northumberland. 1. Feeding ecology and behaviour of the Bar-tailed Godwit - Smith, P C; Evans, P R (Wildfowl, 1973)
An outline is given of the status and feeding ecology of the Bar-tailed Godwit Limosa lapponica at Lindisfarne, Northumberland. Sexual dimorphism in bill-length is pronounced, those of females averaging 30% longer than those of males. Birds feed close to the tide edge, but females tend to feed in deeper water than males. Males feeding in deep water are less successful in capturing prey than males feeding at the tide line, but females are equally successful in both locations. Godwits feed more successfully in flocks than solitarily. Selective advantages of long- and short-billed birds are discussed speculatively.